Oil palm plantations versus mammals and birds conservation: a case study in two oil palm plantations in West Kalimantan Province - Yanto Santosa; Intan Purnamasari (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The assessment of the oil palm plantations impact on biodiversity mostly compares oil palm plantations to natural forests. But in reality, most land cover type before oil palm plantations establishments are no longer primary forest. Observations were made on 2 large holding plantations (PSB) in West Kalimantan Province. Tracking data on the origin of land cover types was carried out by interview method and analysis of interpretation of land-satellite imagery. The results showed that the baseline PSB studied were shrubs/fields and secondary forests. The number of species (mammals and birds) in the oil palm area is higher than the baseline area. PSBs establishment that are originally in the form of shrubs/fields has affect in increasing diversity of mammals (3 species) and birds (11 species). The same results are also shown in areas that are originally in the form of secondary fields and forests, has also increased the number of species of mammals (5 species) and birds (18 species). Thus, it can be concluded that the land cover changes in 2 oil palm plantations studied has a positive impact on the mammals and birds’ species diversity